PENYIKSAAN HEWAN PELIHARAAN SEBAGAI PERBUATAN PIDANA DI KOTA KUPANG - Langkola, Andy Salomo; Pello, Jimmy; Fallo, Debi F. Ng (Petitum Law Journal, 2024)
In essence, cats have the humas right to be treated civilizedly and to receive guarsntees for their walfare in life. In Law Number 41 of 2024, article 1 paragraph (42) defines animal walfare was everything related to the physical and mental condition of animals in accordance with thr animal’s natural behavior. (1) Is animal abuse of cats s criminal act? (2) What are the government’s efforts to deal with the problem of cat abuse in Kupang City? The purpose of this research is to find out whether cat abuse is a criminal act in Kupang City and to find out the government’s efforts in dealing with the problem of cat abuse in Kupang City. The research results show that:(1) Article 302 of the Criminal Code Paragraphs 1 and 2, Article 406 Paragraphs of the Criminal Code, Article 540 of the Criminal Code and the 2023 criminal law book (UU Number 1 of 2023) in the sixth part, namely article 336, article 337 and article 338 of the new Criminal Code also regulates criminal acts of harassment, recklessness and mistreatment of animals. (2) The Kupang City government’s efforts to deal with the problem of cat abuse are to provide socialization and legal education to the community to increase public awareness about animal protection, including the human rights that animals have. Based on the discussion above, the suggestions that researchers give are: the government needs to strengthen laws regarding legal enforcement against cases of animal violence and increase socialization and legal education related to animal rights.